Bidding Strategy of a Flexible CHP Plant for Participating in the Day-Ahead Energy and Downregulation Service Market - He Cui (IEEE, 2021)
To integrate renewable energy generation from wind and solar radiation, most combined heat and power (CHP) plants in northern China are undergoing large-scale upgrades and retrofitting to improve operational flexibility. Simultaneously, the downregulation service (DRS) market is still retained in the day-ahead market in many provinces. Considering a flexible CHP plant with multiple types of coal-fired CHP units and heat storage as a price taker, this paper establishes a collaborative bidding strategy for the CHP plant to participate in both the day-ahead energy market and day-ahead DRS market. The bidding strategy includes the optimal output decision model, power output range model, capacity segmenting model, and bidding models for two markets determined by the marginal generation cost (MGC) and the marginal downregulation cost (MDRC), respectively. These models are validated based on realistic data from a CHP plant in Northeast China.